A three port bidirectional DC-DC converter for PV – Battery – DC microgrid application using fuzzy logic control. (2022) - Ramesh, P.; Gouda, Pramod Kumar; Lakshmikhandan, K.; Ramanathan, G.; Bharatiraja, C.
Highlights: The system structure of a DC micro grid and its unit functional models are first introduced in this paper. Second, depending on the various power demand scenarios, an appropriate control action is maintaining the power for charging. The proposed fuzzy is operating in a decentralized manner for maintaining the power distribution between micro grid DC-link and ESU. The overall PV tied with DC micro grid charging station control system is studied under various practical circumstances such as low and full PV array power production, grid overloading, and local energy storage and, EV to EV. Abstract: Electric vehicles (EVs) have emerged as cutting-edge technology in mainstream transportation. But, the accessibility of opportunities to charge the battery cells has become a contentious issue. Even though EVs are constituted a dynamic load, regulating available grid electricity or sustainable assisted electricity generation to recharge EVs incorporates a range of variables. This study represents the hierarchy of a DC microgrid, unit concepts and methods. Finally, an effective control action is to maintain the power for charging, depending on multiple energy usage circumstances. The proposed fuzzy operate decentralized to maintain power distribution between the microgrid DC-link and the ESU. The total PV coupled with the DC microgrid charging point control system is investigated under a variety of realistic conditions such as low and full PV array energy production, network overflowing, existing energy storage, and vehicle to vehicle. The laboratory-scale MATLAB/Simulink simulation and experimental of multiple EV charging plug spot DC microgrid has been studied and validated under numerous different microgrid settings, and they coincide with the suggested charging station upshot.